Governança comunitária indígena dos recursos hídricos e relação com a saúde na região do Baixo São Marcos, Roraima - Barreto, Fabrício (2023)
The interest in knowledge of governance by indigenous peoples over their resources, and the incidence of waterborne diseases was the starting point for this thesis. In indigenous communities in the rural area of Boa Vista, Roraima, Brazil, the incidence of waterborne diseases is high. Thus, the desire to contribute to the quality of life of indigenous peoples arose, based on an investigation of their problems, in the search for solutions. The starting point was the water of these communities and the possible relationship with waterborne diseases, considering the governance of water resources. In order to analyze the community governance of water resources in the region, a historical account of the cultural aspects of the indigenous peoples was carried out, between 1787 and 1991. This period describes the history of this region from the colonization of the state of Roraima to the demarcation of the indigenous land, in mid-1990s. The sanitation and water conditions of the communities studied were also analyzed, as well as potability and the relationship with health. Finally, there is a search for a solution to minimize the problems of contamination of water resources, including the description of the strategy of a given community for water treatment. This action resulted in innovation in water treatment in a community, developed from the knowledge of an indigenous sanitation agent. All these themes presented generated five articles, according to the methodological proposal of presenting the thesis in the format of articles. As a methodology, it was a descriptive study of mixed methods, with a qualitative and quantitative approach, with each article having a specific methodology to achieve its objectives. The 12 communities of the São Marcos Indigenous Land in the Baixo São Marcos region were defined for the study area, from where water from five points was analyzed: community artesian well, school, health center, water tank and residence indicated by leaders, with some exceptions, also analyzing water from wells, lakes, streams and even larger rivers, which were used for human consumption. As a result, it was observed that the waters of 10 communities were unfit for human consumption, due to the high amount of heterotrophic bacteria or density of E. coli, being related to the most severe diarrheal conditions, mainly in children. It is concluded that strategies for monitoring water quality, improvements in sanitation conditions and the autonomy of indigenous peoples for the governance of their water resources need to be encouraged and implemented. Indigenous peoples must be guaranteed the maintenance of their lives with more quality and respect for their traditions, but with technological advances that guarantee their rights and living conditions that promote well-being in their lands.